2017
DOI: 10.5935/0101-2800.20170008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic tests for cytomegalovirus active infection in renal transplant recipients

Abstract: Our data demonstrate that both methods are suitable and have almost equivalent accuracy for the detection of post-transplant cytomegalovirus replication. The choice for either test must take in consideration the demand, execution capability and cost-effectiveness at each institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
5
5
1
Order By: Relevance
“…Previous retrospective studies have described other risk factors for CMV recurrence such as D+/R− serostatus, acute rejection treatment, and diabetes mellitus, which were not found in our study. Nevertheless, we observed a higher relapse rate in patients with primary CMV infection compared to those with recurrent infection.…”
Section: Discussioncontrasting
confidence: 79%
“…Previous retrospective studies have described other risk factors for CMV recurrence such as D+/R− serostatus, acute rejection treatment, and diabetes mellitus, which were not found in our study. Nevertheless, we observed a higher relapse rate in patients with primary CMV infection compared to those with recurrent infection.…”
Section: Discussioncontrasting
confidence: 79%
“…The evaluation of the correlation between the two diagnostic methods showed that they have a good correlation. This is in agreement with previous comparisons between pp65 antigenemia and PCR for the diagnosis of active CMV infection [33][34][35][36][37].…”
Section: Discussionsupporting
confidence: 93%
“…The incidence rates found in Brazil are similar to studies in Japan (70.8%) 16 and India (73.7%) 17 but differ from countries such as Korea, where the literature shows rates of 30-40% [18][19][20][21] , Finland of 27% 22 and in the USA, in a pediatric kidney transplant population, a rate of 27% was found. 23 The comparison between the two diagnostic tests performed in this study showed a concordance between the results of 70.3%, in agreement with previous studies that demonstrated concordances ranging from 66.6-94.3% 11,15,[18][19][20][23][24][25] . However, most of these studies were performed before the advent of the WHOIS, as well as before the knowledge of factors related to the presentation of the virus in different biological matrices 5,26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…Considering the patients in this study with positive qPCR results who had negative performed in the same institution in 2004 using CMV antigenemia as a diagnostic tool observed 60.0% of infection and 38.4% of disease 10 . In a study carried out in another hospital in the same city in Brazil, with a composition of patients that was similar to that of this study, the incidence of CMV infection was 53.3% 11 . This cohort was characterized by an elevated seroprevalence of CMV infection in both donors and recipients, and by a limited proportion of patients on universal anti-CMV prophylaxis (16.6% of patients in comparison to 50.0% in the study by Franco et al (2017) 11,12,13 .…”
Section: Discussionsupporting
confidence: 74%